Reinforced Bamboo Nanocomposites using Stabilized Polymers: Characterizations and Optimization - Muhammad, Adamu (Universiti Malaysia Sarawak, (UNIMAS), 2021)
Bamboo is an abundant natural resource in Malaysia that has prospect to substitute wood in many engineering applications. However, there are drawbacks such as poor physicomechanical properties, susceptibility to damage, frequent costly maintenance, deterioration of physical and mechanical properties due to environmental variation. In this work, the effects of montmorillonite nanoclay and combination of stabilized polymers such as poly(ethylene-alt-maleic anhydride) (PEA), polyvinyl alcohol (PVA), polyvinyl alcohol-coacrylonitrile, and polyvinyl alcohol-co-styrene on formulation of bamboo nanocomposites were investigated and optimized using response surface methodology. When poly(ethylenealt-maleic anhydride) was used, functional groups in the raw bamboo and nanocomposites were identified using Fourier transform infrared spectroscopy (FTIR). X-ray diffraction XRD) plots showed the prominent peak intensity at a diffraction angle of 73° due to the transformation of the amorphous structure to a crystalline structure in the prepared nanocomposite. The morphologies of the raw bamboo and the nanocomposites were compared using scanning electron microscopy (SEM) analysis. There was an increase in the modulus of elasticity (MOE) from 7.82 GPa to 18.96 GPa and a corresponding increase in the modulus of rupture (MOR) from 68.67 MPa to 121.48 MPa of the raw bamboo to the nanocomposites, respectively. There was also improvement in the thermal properties from the differential scanning calometry (DSC) and thermogravimetric (TGA) results. Similarly, for PVA formulated bamboo nanocomposites, The FTIR spectra of the nanocomposites indicated incorporation of the polymer and nanoclay in the structure and diffractograms from XRD also indicated higher crystallinity of the prepared nanocomposites compared to raw bamboo. The SEM image revealed that of the lumens of the raw bamboo were filled by the polymer and nanoclay after formation of the nanocomposites.